Model Pembelajaran Problem Possing melalui Pembelajaran Daring Zoom untuk Mengajarkan “Peluang Suatu Kejadian” pada Siswa Kelas XII Sman 1 Kademangan Kabupaten Blitar - Bambang Tumojo (Jurnal Pendidikan : Riset dan Konseptual, 2021)
This study took the initiative to apply a learning model that combines cooperative learning, requires high reasoning power and utilizes communication technology that is packaged in the form of CAR using a problem possing learning model through online learning zoom. This research was conducted at SMAN 1 KADEMANGAN in the even semester of 2020/2021. The results of this study indicate that the learning process with a problem possing model through online zoom learning can increase creativity and train students to have high discipline, responsibility, and can train students to think at high levels (high order thinking) and train verbal skills because they are trained to present the result of their work. This learning model can also motivate students to take advantage of technological facilities (laptops and cellphones) with a zoom application in the learning process, so that students are accustomed to using technology.